Implementation of Solutions a Simple Claims of Sharia Economy in the Religious Court of Malang City and Religious Court of Malang District - Zuhriah, Efaniah; Fuadi, Suud; Sukadi, Imam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The settlement of a simple lawsuit on Islamic economic matters in the Malang City Religious Court and Malang District Religious Court is in line with the principle of conducting a simple trial. The procedure is simpler because it is more concise, with no claims for provisions, exceptions, reconventions, interventions, replicas, duplicates or conclusions. The settlement time is also limited to a maximum of 25 days. Costs will also be cheaper because the process and time of settlement are simple. Constraints faced in the settlement of a simple lawsuit in sharia economic matters in Malang City Religious Court and Malang District Religious Court include the first, Jurisdictional Problems. Secondly, a simple suit cannot be effective if there is a resistance suit. Third, careful examination of case files by the Registrar.